Effect of Nebivolol and Olmesartan on 24-Hour Brachial and Aortic Blood Pressure in the Acute Stage of Ischemic Stroke. (7th October 2019) - Georgianou, Eleni; Georgianos, Panagiotis I.; Petidis, Konstantinos; Markakis, Konstantinos; Zografou, Ioanna; Karagiannis, Asterios
Abstract : Background . Elevated blood pressure (BP) in the acute phase of ischemic stroke is associated with heightened risk of early disability and death. However, whether BP-lowering in this setting is beneficial and the exact levels at which BP should be targeted remain unclear. This study aimed to evaluate the effect of nebivolol, olmesartan, and no-treatment on 24-hour BP in patients with hypertension during the acute poststroke period. Methods . In a single-blind fashion, 60 patients with acute ischemic stroke and clinic systolic BP (SBP) 160–220 mmHg were randomized to nebivolol (5 mg/day), olmesartan (20 mg/day), or no-treatment between Day 4 and Day 7 of stroke onset. BP-lowering efficacy was assessed through 24-hour BP monitoring using the Mobil-O-Graph device (IEM, Germany). Results . Between baseline and Day 7, significant reductions in 24-hour brachial SBP were noted with nebivolol and olmesartan, but not with no-treatment. Change from baseline (CFB) in 24-hour brachial SBP was not different between nebivolol and olmesartan groups (between-group difference: −3.4 mmHg; 95% confidence interval (CI): −11.2, 4.3), whereas nebivolol was superior to no-treatment in lowering 24-hour brachial SBP (between-group difference: −7.8 mmHg; 95% CI: −7.8 mmHg; 95% CI: −15.6, −0.1). Similarly, nebivolol and olmesartan equally lowered 24-hour aortic SBP (between-group difference: −1.9 mmHg; 95% CI: −10.1, 6.2). Nebivolol and olmesartan provoked similar reductions in 24-hour heart rate-adjusted augmentation index and pulse wave velocity. Conclusion . This study suggests that during the acute phase of ischemic stroke, nebivolol is equally effective with olmesartan in improving 24-hour aortic pressure and arterial stiffness indices. ClinicalTrials.gov identifier number:NCT03655964 .